Multi-mechanism synergistic remediation of phosphate-solubilizing bacteria under tetracycline and lead co-contamination stress: phosphate precipitation and organic acid complexation - Zhou, Yanjie; Wu, Jiangyan; Tang, Qi; Chen, Huihui; Liu, Yuan; Chen, Haoming (Frontiers in Microbiology, 2026)
Tetracycline (TC) and lead (Pb) contamination have become globally urgent environmental challenges. They are widely distributed in soil, water bodies, and other environments, posing severe threats to ecosystems and human health. Microbial remediation, as a cost-effective and environmentally friendly pollution control approach, has garnered increasing attention in recent years. This study isolated and screened a highly efficient phosphate-solubilizing bacteria strain CZ-M3 (Microbacterium sp.) from a chemical factory contaminated environment. The strain achieved a phosphate solubilization capacity of 125.46 mg/L in PVK medium, significantly outperforming the control strain CZ-B5 (69.1% increase). Stress tolerance experiments demonstrated that strain CZ-M3 maintained robust activity under TC (≤200 mg/L) and Pb2+ (≤1,000 mg/L) stress, achieving 72-h removal rates of 57.36% for 200 mg/L TC and 28.5% for 1,000 mg/L Pb2+, thus selected as the core functional strain for remediating TC-Pb co-contamination. Notably, under co-contamination conditions, TC stress was found to stimulate Pb immobilization by CZ-M3. First, the strain releases PO₄3− by secreting various organic acids, forming stable Pb-phosphate precipitates [e.g., Pb₅ (PO₄)₃Cl] with Pb2+, which was confirmed by X-ray diffraction (XRD) and attenuated total reflectance infrared spectroscopy (ATR-IR) results. Second, three-dimensional excitation-emission matrix (3D-EEM) spectroscopy revealed that combined stress induced enhanced secretion of extracellular polymeric substances (EPS) (humic acid-like substances), whose abundant functional groups (e.g., carboxyl and hydroxyl groups) effectively complexed and adsorbed contaminants. Most critically, organic acid secretion profiling found that high-concentration TC stress inhibited the tricarboxylic acid (TCA) cycle, causing a significant increase in tartaric acid content (significantly higher than the control group). Tartaric acid formed stable complexes with Pb2+ via its functional groups and promoted phosphate precipitation. This study provides a solid theoretical basis and a valuable microbial resources for the bioremediation of heavy metal-antibiotic co-contaminated environments.